Pengaruh Sales Promotion, Brand Image, Online Customer Review di TikTok terhadap Keputusan Pembelian Fore Coffee Cabang BG Junction Mall Surabaya - Kirana Laksmi Davina; Awin Mulyati; Agung Pudjianto (Politeknik Kampar, 2025)
This study aims to test and analyze the Influence of Sales Promotion, Brand Image, and Online Customer Review on the TikTok Application on the purchase decision of Fore Coffee products. This study uses a quantitative approach method used by distributing questionnaires via Google Form to 100 respondents. The population in this study were Young Generation Consumers who had purchased products from Fore Coffee at BG Junction Mall, Surabaya City. The sampling method used in this study was the Probability Sampling method. The sampling technique used was Accidental Sampling. The analysis technique used was multiple linear regression analysis. The findings show that partially and simultaneously Sales Promotion, Brand Image, and Online Customer Review influence Purchase Decisions in young generation consumers who have purchased products from Fore Coffee at BG Junction Mall, Surabaya City..